PEMANFAATAN E-COMMERCE BUSINESS TO CONSUMER (B2C) MARKETPLACE UNTUK PENGEMBANGAN USAHA MIKRO,KECIL DAN MENENGAH (UMKM) - Dono Saputro, Prasetyo (Journal Knowledge Industrial Engineering (JKIE), 2020)
In welcoming the Industrial Revolution 4.0 marked the era of the digital economy (Digital Economy Era). The new economic era is characterized by the application of information technology in carrying out its economic activities. Internet users in Indonesia aged 13-18 years = 16.68%, age 19-34 years = 49.52%, age 35-54 years = 29.55%, age> 54 years = 4.24%. And the number of internet users by sex, male gender is = 51.43%, female gender is = 48.57%. The use of the internet today has even penetrated into the e-commerce market place system which is a sale and purchase of goods / services through electronic networks (internet). Transactions through e-commerce involve 3 parties, namely: suppliers / partners, website managers (our company), and customers (customers). The data on internet usage are as follows: looking for prices = 45.12%, helping jobs = 41.04%, buying information = 37.82%, buying online = 32.19%, looking for work = 26.19%, banking transactions = 17.04%, selling online = 16.83%. The stages that occur in e-commerce market place are: (1) Orders are made online (carried out by the buyer); (2) Confirming payment (carried out by the buyer); (3) Checking the condition of the stock of goods (carried out by the seller); (4) Arranging the delivery of goods (arranging shipping services provided by the e-commerce marketplace system, usually carried out by the seller); e-commerce market place, the goal is that customer trust can be achieved / fulfilled)